Sustainable Food Systems Through Livestock–Pasture Integration - Monde Rapiya; Mthunzi Mndela; Abel Ramoelo (Agriculture)
The world’s population is projected to rise significantly, which poses challenges for global food security due to increased demand for food, especially from livestock products. As incomes grow in lower-income countries, there is a shift towards more diverse diets that include meat and dairy, stressing our agricultural systems. Livestock plays a crucial role in food production, contributing about 16% of dietary energy, and effective pasture management is vital for enhancing livestock productivity. This review explores how integrating pasture and livestock management can create sustainable food systems and improve nutrition and livelihoods. It assesses the economic viability of pasture-based livestock systems and examines how climate change affects both pasture productivity and livestock performance. The review also identifies innovative practices, such as improved grazing management and technological advancements, that can improve pasture health and livestock output. The findings underscore the importance of well-managed pastures, which can restore degraded lands, improve animal welfare, and support food security. It also highlights that adaptation strategies are necessary to address the challenges posed by climate change, ensuring that livestock systems remain sustainable. By focusing on innovative practices and better management, we can meet the growing demand for animal products while preserving ecosystems and promoting economic stability. Overall, this review emphasizes the need for a holistic understanding of how livestock and pasture management can work together to enhance food security in a changing world.